PENGARUH INOVASI STRATEGI PEMASARAN TERHADAP KEPUASAN PELANGGAN: STUDI KASUS PADA UMKM KOPI JAGO - Andreas Andreas; Sri Herlina Aprilyana; Keshya Amanda Putri; Miftahul Ulum; Timotius Bulu (MANAJEMEN, 2025)
This study aims to analyze the influence of marketing strategy innovation on customer satisfaction at the MSME "Kopi Jago." Amid increasingly intense business competition, marketing innovation has become a key factor in maintaining and enhancing customer loyalty. This research employs a quantitative method with data collected through questionnaires distributed to 50 respondents. The data analysis techniques used include validity testing, reliability testing, simple linear regression analysis, t-test, and coefficient of determination (R²) test, assisted by SPSS 25. The results indicate that marketing strategy innovation has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.778, indicating a strong positive relationship.. The significance value of 0.000 < 0.05 and the R² value of 0.405 indicate that marketing strategy innovation explains 40.5% of the variation in customer satisfaction. indicating that effective marketing innovations enhance customer satisfaction at Kopi Jago